Long Noncoding RNA uc001pwg.1 Is Downregulated in Neointima in Arteriovenous Fistulas and Mediates the Function of Endothelial Cells Derived from Pluripotent Stem Cells - Lei Lv; Haozhe Qi; Xiangjiang Guo; Qihong Ni; Zezhen Yan; Lan Zhang (Stem Cells International)
Recent studies indicate important roles for long noncoding RNAs (lncRNAs) as essential regulators of gene expression. However, the specific roles of lncRNAs in stenotic lesions of arteriovenous fistula (AVF) failure are still largely unknown. We first analyzed the expression profiles of lncRNAs in human stenosed and nonstenotic uremic veins using RNA-sequencing methodology. A total of 19 lncRNAs were found to be differentially expressed in stenotic lesions. Among these, uc001pwg.1 was one of the most significantly downregulated lncRNAs and enriched in both control vein segments and human umbilical vein endothelial cells (HUVECs). Further studies revealed that uc001pwg.1 overexpression could increase nitric oxide synthase (eNOS) phosphorylation and nitric oxide (NO) production in endothelial cells (ECs) derived from human-induced pluripotent stem cells (HiPSCs). Mechanistically, uc001pwg.1 improves endothelial function via mediating MCAM expression. This study represents the first effort of identifying a novel candidate lncRNA for modulating the function of iPSC-ECs, which may facilitate the improvement of stem cell-based therapies for AVF failure.